Adaptive Bit-Map Correlation in the Ambtc-Vq Techniques Using an Algorithm for Binary Codebook Design - Hameed, Maha A; Ismael, Ban S; Ali, Hasanain H (Al-Nahrain Journal of Science, 2011)
In this paper, The coding performance of the VQ method (which is suggested to code the output bit-map produced from the AMBTC technique) will be improved by finding an adaptive method for binary codebook designation which is totally depends on an individual local original image statistics; that is generate a new codebook for each individual coded binary image (bit-map). An application of this coding method is that performed on digital video image sequence. In this paper, we have introduced anew calibration (i.e. adaptive bit-map correlation (ρ)) which must distinguish between the decoding bit-map using VQ technique and the original bit-map (the output from the AMBTC method). From the experimental results affixed binary codebook of size 64 code words, utilizing block of size 4x4, the expected rate will be fall from 2 b/p into 1.375 b/p.